(untitled) (Medico Legal Update, 2021)
The development of endowment land in Indonesia is very rapid which is directly proportional to the problems that occur regarding endowment. The resolution of this endowment dispute is based on the charity law, carried out by deliberation and mediation. In some cases, the mediation conducted was not following the existing mediation rules so that eventually the resolution of the endowment dispute became ineffective. It is important to study the problem of the resolution of endowment disputes through mediation from the perspective of the theory of legal effectiveness. This study aims to understand and analyze the problematic of endowment dispute resolution through mediation from the perspective of the theory of legal effectiveness in Central Java. The research method used is socio-legal research, with an empirical juridical approach and includes qualitative research. The results of this study are the settlement of endowment disputes through mediation outside the court according to the theory of legal effectiveness, not yet effective, because there are no formal legal rules. It is necessary to make regulations for the implementation of non-litigation mediation, to provide practical guidance for the implementation of mediation in the community